A self-compatible pear mutant derived from γ-irradiated pollen carries an 11-Mb duplication in chromosome 17 - Nishio, Sogo; Shirasawa, Kenta; Nishimura, Ryotaro; Takeuchi, Yukie; Imai, Atsushi; Mase, Nobuko; Takada, Norio (Frontiers in Plant Science, 2024)
Self-compatibility is a highly desirable trait for pear breeding programs. Our breeding program previously developed a novel self-compatible pollen-part Japanese pear mutant (Pyrus pyrifolia Nakai), '415-1', by using γ-irradiated pollen. '415-1' carries the S-genotype S4dS5S5, with "d" indicating a duplication of S5 responsible for breakdown of selfincompatibility. Until now, the size and inheritance of the duplicated segment was undetermined, and a reliable detection method was lacking. Here, we examined genome duplications and their inheritance in 140 F1 seedlings resulting from a cross between '515-20' (S1S3) and '415-1'. Amplicon sequencing of S-RNase and SFBB18 clearly detected Shaplotype duplications in the seedlings. Intriguingly, 30 partially triploid seedlings including genotypes S1S4dS5, S3S4dS5, S1S5dS5, S3S5dS5, and S3S4dS4 were detected among the 140 seedlings. Depth-of-coverage analysis using ddRAD-seq showed that the duplications in those individuals were limited to chromosome 17. Further analysis through resequencing confirmed an 11-Mb chromosome duplication spanning the middle to the end of chromosome 17. The duplicated segment remained consistent in size across generations. The presence of an S3S4dS4 seedling provided evidence for recombination between the duplicated S5 segment and the original S4 haplotype, suggesting that the duplicated segment can pair with other parts of chromosome 17. This research provides valuable insights for improving pear breeding programs using partially triploid individuals.